Babae sa bintana - Roño, Chito; Monteverde, Lily.; Gomez, Richard; Roces, Rosanna; Estrada, John.; Regal Films (Quezon City Regal Films, 1999)
Jack, a sexy lone mysterious woman who lives in an apartment adjacent to Mitch's. Mitch finds himself drawn to the strange, beautiful neighbor next door. Teo, a police who is Jack's lover. Bagyo a ruthless rotten officer with ties to the underworld and Teo's boss. Mitch gives in to his curiousity and the sensual that lies behind Jack's window.Voyeurism's detected vicariousness losses its zing and pure passion take over. As Mitch treads on treacherous grounds beyond Jack's window we see the blunder turn int his biggest, deadliest mistake. For not long after, all hell breaks loose.
VCD
Story & screenplay by Roy Iglesias, executive producers Lily Monteverde, directed by Chito Rono.
Richard Gomez, Rosanna Roces, John Estrada.
Keywords: Feature films